New fowler-nordheim injection, charge neutralization, and gamma tests on the REM RFT300 RADFET dosimeter - Lipovetzky, José (2012)
Through the injection of a Fowler-Nordheim tunnel current or the inversion of oxide fields during irradiation (Radiation-Induced Charge Neutralization), the oxide charge trapped in thick-oxide (300 nm) commercial RADFETs, often called QOT could be erased. Novel trapped-hole and interface characteristics were observed after treatments of this type at high doses. With both erasure techniques, it was possible only to neutralize a fraction of the oxide trapped charge. A non negligible amount of charge and border traps is deemed here to be ?intractable?. That adjective an a symbol, QIN, are introduced for the first time in this paper. Later sections discuss the possible impact of these results. The conclusion for dosimetry is that a ?reusable RADFET? dosimeter, working up to an unprecedented dose before wearing out, may be a practical possibility.